Multi-relay Antennas for Energy Harvesting Cognitive Radio Networks using Energy-Assisted Decode Forward Method - Priyanka, Yadlapalli; Arthi, R (International Journal of Engineering and Technology, 2018)
The single antenna relay energy-assisted decode forward (EDF) was not applicable for multi cognitive users that has less data rates. In order to achieve higher data rates with increased user demands energy harvesting or Simultaneous Wireless Information and Power Transfer (SWIPT) enabled networks with multi antenna relays are highly recommended. The proposed work considers multi relay EDFSWIPT for 5G systems with presence of transmitter and an antenna array. The transmitter affords information and energy to various multiple single-antenna secondary receivers (SR). The SR outfitted with a power splitter receiving system where multiple primary relays are introduced. The goal of proposed work is to amplify weighted sum rate harvested energy for SR using multi relay EDF. The simulation considers the capacity, outage probability, and throughput for both primary and secondary networks with respect to both single multi relay EDF. The simulation results afford that multi relay EDF has better performance than single antenna array EDF.Â